Strategi Pengurus Pesantren dalam membina Akhlak Karimah Santri di Asrama Al Banat Purwakarta - Listivia Yunanda; Dedih Surana; Fitroh Hayati (UNISBA Press, 2024)
Abstract. This research aims to find out the strategies used by administrators in developing the morals of students. The moral development of students in Islamic boarding schools aims to form characters that are in accordance with Islamic teachings. Instilling morals in students and implementing them is not an easy thing, so several stages are needed to instill these morals. Because the main goal of akhlak karimah is to form a person who is religiously devout and has noble character according to Islamic teachings. The research method applied in this thesis is qualitative with a descriptive approach. The researcher aims to describe the situation that will be observed in the field more specifically, transparently and in depth. The data collection techniques used involved observation, interviews and documentation studies. The data analysis process involves data collection, data reduction, data presentation, and drawing conclusions. The results of this research can be concluded that the approach in developing the morals of students at the Al Banat hostel in Purwakarta prioritizes the concept of being a good example, where the boarding school administrators act as role models to inspire students to follow positive footsteps. The implementation of moral development is carried out through the activities of studying the Banin akhlakulil book and watching the stories of the prophets in films. Moral development methods are applied, such as providing role models, advice, habits and rewards. This method not only focuses on changing behavior, but also on building strong character and applying moral values in everyday life. Evaluation of moral development is carried out verbally, involving a personal approach between students and administrators. This assessment includes observing behavior, social interactions, and implementing moral values in daily activities. In this way, administrators can understand developments students' morals and the extent to which the values taught are reflected in their actions and attitudes. Keywords: Strategy, Coaching, Karimah Morals. Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana strategi yang digunakan oleh pengurus dalam membina akhlak santri. Pembinaan akhlak santri di pesantren bertujuan untuk membentuk karakter yang sesuai dengan ajaran Islam. Dengan menanamkan akhlak pada santri dan untuk menerapkannya bukanlah hal yang mudah, maka diperlukan beberapa tahapan dalam menanamkan akhlak tersebut. Karena tujuan utama akhlak karimah yaitu membentuk pribadi yang taat beragama dan berakhlak mulia sesuai ajaran Islam. Metode penelitian yang diterapkan dalam skripsi ini adalah kualitatif dengan pendekatan deskriptif. Peneliti bertujuan untuk menggambarkan situasi yang akan diamati di lapangan dengan lebih spesifik, transparan, dan mendalam. Teknik pengumpulan data yang digunakan melibatkan observasi, wawancara, dan studi dokumentasi. Proses analisis data melibatkan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini dapat disimpulkan bahwa pendekatan dalam membina akhlak santri di asrama Al Banat Purwakarta mengedepankan konsep menjadi contoh yang baik, di mana pengurus pesantren berperan sebagai teladan untuk menginspirasi santri mengikuti jejak yang positif. Pelaksanaan pembinaan akhlak dilakukan melalui kegiatan mengaji kitab akhlakulil banin dan menonton kisah para nabi dalam film. Metode pembinaan akhlak yang diterapkan, seperti memberikan tauladan, nasihat, pembiasaan, dan ganjaran. Metode ini tidak hanya berfokus pada perubahan perilaku, tetapi juga pada pembentukan karakter yang kuat dan penerapan nilai-nilai akhlak dalam kehidupan sehari-hari. Evaluasi pembinaan akhlak dilakukan secara verbal, melibatkan pendekatan personal antara santri dan pengurus. Penilaian ini mencakup pengamatan perilaku, interaksi sosial, dan implementasi nilai-nilai akhlak dalam aktivitas sehari-hari. Dengan demikian, pengurus dapat memahami perkembangan akhlak santri dan sejauh mana nilai-nilai yang diajarkan tercermin dalam tindakan dan sikap mereka. Kata Kunci: Strategi, Pembinaan, Akhlak Karimah.